The effect of UV-radiation on photo-oxidants and formaldehyde in the atmosphere - Riedel, K.; Weller, Rolf; Schrems, Otto (2002)
The annual cycle of formaldehyde (HCHO) has been investigated at a remote surface-site in Antarctica. HCHO mixing ratios during the period of stratospheric ozone depletion are significantly higher than during times of similar sunshine duration in austral autumn. This might be due to enhanced UV-B radiation.